Seasonal Variation in Biomass and Production of the Macrophytobenthos in two Lagoons in the Southern Baltic Sea - Paar, Martin; Berthold, Maximilian; Schumann, Rhena; Dahlke, Sven; Blindow, Irmgard (Frontiers in Earth Science, 2021)
Baltic coastal lagoons are severely threatened by eutrophication. To evaluate the impact of eutrophication on macrophytobenthos, we compared the seasonal development in macrophytobenthic composition, biomass and production, water column parameters (light, nutrients), phytoplankton biomass and production in one mesotrophic and one eutrophic German coastal lagoon. We hypothesized that light availability is the main driver for primary production, and that net primary production is lower at a higher eutrophication level. In the mesotrophic lagoon, macrophytobenthic biomass was much higher with distinct seasonal succession in species composition. Filamentous algae dominated in spring and late summer and probably caused reduced macrophytobenthic biomass and growth during early summer, thus decreasing vegetation stability. Light attenuation was far higher in the eutrophic lagoon, due to high phytoplankton densities, explaining the low macrophytobenthic biomass and species diversity in every season. Areal net primary production was far lower in the eutrophic lagoon. The “paradox of enrichment” hypothesis predicts lower production at higher trophic levels with increased nutrient concentrations. Our results prove for the first time that this hypothesis may be valid already at the primary producer level in coastal lagoons.